The road to 6G: a comprehensive survey of deep learning applications in cell-free massive MIMO communications systems - Lazaros Alexios Iliadis; Zaharias D. Zaharis; Sotirios Sotiroudis; Panagiotis Sarigiannidis; George K. Karagiannidis; Sotirios K. Goudos (EURASIP Journal on Wireless Communications and Networking, 2022)
Abstract The fifth generation (5G) of telecommunications networks is currently commercially deployed. One of their core enabling technologies is cellular Massive Multiple-Input-Multiple-Output (M-MIMO) systems. However, future wireless networks are expected to serve a very large number of devices and the current MIMO networks are not scalable, highlighting the need for novel solutions. At this moment, Cell-free Massive MIMO (CF M-MIMO) technology seems to be the most promising idea in this direction. Despite their appealing characteristics, CF M-MIMO systems face their own challenges, such as power allocation and channel estimation. Deep Learning (DL) has been successfully employed to a wide range of problems in many different research areas, including wireless communications. In this paper, a review of the state-of-the-art DL methods applied to CF M-MIMO communications systems is provided. In addition, the basic characteristics of Cell-free networks are introduced, along with the presentation of the most commonly used DL models. Finally, future research directions are highlighted.